2020
DOI: 10.1002/pon.5503
|View full text |Cite
|
Sign up to set email alerts
|

Distress and problem assessment among people living with cancer from Culturally and Linguistically Diverse backgrounds

Abstract: Objective: To examine whether routine assessment of distress, recommended as part of comprehensive cancer care, is utilised equally with culturally and linguistically diverse (CALD) vs non-CALD people living with cancer. Methods: A medical records review of all patients attending cancer-specific treatment units at a single tertiary hospital in Melbourne, Australia between 2015-2018. Recording of administration of the Distress Thermometer and Problem Checklist (DT and PC) was extracted for all patients. Details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cancer survivors from rural areas experience high-levels of cancer-related distress (the multifactorial, unpleasant, emotional experience that interferes with their ability to cope with cancer, treatment, and symptoms effectively). As recently as 10 years ago, fewer than 10% of all individuals with cancer were being screened for cancer-related distress, but with wider adoption of screening tools such as the National Comprehensive Cancer Network Distress Thermometer and Problem List [ 1 ], as many as 70% of individuals with cancer are now being screened [ 2 - 4 ]. Unfortunately, despite this high rate of screening, difficulty connecting rural survivors with psychosocial support persists.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer survivors from rural areas experience high-levels of cancer-related distress (the multifactorial, unpleasant, emotional experience that interferes with their ability to cope with cancer, treatment, and symptoms effectively). As recently as 10 years ago, fewer than 10% of all individuals with cancer were being screened for cancer-related distress, but with wider adoption of screening tools such as the National Comprehensive Cancer Network Distress Thermometer and Problem List [ 1 ], as many as 70% of individuals with cancer are now being screened [ 2 - 4 ]. Unfortunately, despite this high rate of screening, difficulty connecting rural survivors with psychosocial support persists.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst certain cultural lifestyle factors may potentially enable better symptom management and therefore explain the reduced likelihood to experience fatigue, it is difficult to elucidate the true causation as literature regarding symptom distress in culturally and linguistically diverse (CALD) cancer patients is limited and conflicting. For example, one study found that migrants with cancer were more likely to report worse health-related QoL and higher emotional distress compared to Anglo-Saxon patients [ 31 ], whilst another found that CALD patients reported a similar level of symptom distress (measured through the Distress Thermometer and Problem Checklist) to non-CALD patients [ 32 ]. Similar to our findings, a recent study using PCOC data reported that cancer patients preferring non-English languages were less likely to report symptoms or problems, except for family/carer problems [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These difficulties are compounded in the CALD population by language and cultural barriers in addition to lower health literacy ( Leung et al, 2014 ; Ng & Omariba, 2010 ). There is a large body of evidence regarding the benefits of patient-reported outcome (PRO) screening, including facilitating discussions around patients’ supportive care needs and decreased symptom severity ( Howell et al, 2015 ; Jack et al, 2013 ; Kotronoulas et al, 2014 ; Skaczkowski et al, 2020 ). The screening of PRO, using standardized self-administered questionnaires, is undertaken in both CALD and non-CALD populations.…”
Section: Discussionmentioning
confidence: 99%
“…The screening of PRO, using standardized self-administered questionnaires, is undertaken in both CALD and non-CALD populations. However, evidence indicates that there are differences in how CALD patients complete these questionnaires (e.g., family members complete the questionnaire), which might limit the benefits of PRO screening ( Skaczkowski et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%